Indonesia Matters : Diversity, Unity and Stability in Fragile Times. - Nguyen, Thang D. (Marshall Cavendish International (Asia) Ptd Ltd., 2003)
The recent years for Indonesia have been especially tumultuous in terms of its political directions, its economy and its social stability. What impact does all the changes have on Indonesia now and on its future? This is a timely publication with contributions from various experts and leaders on Indonesia's political, economic and social changes since the fall of President Suharto, a sharp assessment of its current challenges, and a comprehensive outlook on its future. The book will be useful background references for policy-makers, business investors, researchers and students in tertiary inst.